Development and characterization of introgression lines of an indica-type rice variety, IR64, for unique agronomic traits (JIRCAS, 2010)
Contents: Breeding scheme of development of the INLs, genetic characterization of INLs, phenotypic characterization of agronomic traits of INLs,...